Can we grow with our children? The effects of a comprehensive early childhood development program - Britta Rude (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
I exploit the staggered roll-out of a universal early childhood development program in Chile to assess the impact of a comprehensive approach to early childhood development on outcomes in middle childhood. Using variation across time and municipalities, I study outcomes such as school performance, cognitive development, parental stress, household relationships, and health. I use administrative data on students as well as newborns in Chile, standardized test scores of all 4th graders, and an extensive early childhood development survey. I find positive and significant effects on school performance. The effect is less pronounced for girls and the socioeconomically vulnerable population. The improvements in learning outcomes are driven by improvements in intra-household relations. Comprehensive programs are powerful tools but have several flaws.
Keywords: I24; I28; I38; J13; J24; O15; 330; Education and inequality; government policy; children; human capital